The relationship between the WTO and two regional mechanisms in Latin America - Defaz Ontaneda, Maria de Fatima (2021)
The reemergence of open regionalism in recent years has fostered a new scenario in Latin America characterized by greater trade liberalization. Within this context, the World Trade Organization ensures that trade flows as smoothly, predictably and freely as possible, and determines the rules that govern international trade. Based on the open regionalism and notified as regional trade agreements in the multilateral trade system, the Pacific Alliance and the Andean Community proceed according to Article XXIV of the WTO. Article XXIV determines that regional mechanisms focused on a commercial agenda must facilitate trade between its member countries, and not create obstacles to it. In this way, the WTO and a regional mechanism can keep a linkage. This research argues that while the Pacific Alliance and the WTO are formally linked, the Andean Community and the WTO are indirectly linked.